Diversity and foraging activity of coffee insect pollinators in land near and far from the forest of North Sumatra, Indonesia - RIKA ROULINA SINAGA; NINA MARYANA; PURNAMA HIDAYAT (Society for Indonesian Biodiversity, 2024)
Abstract. Sinaga RR, Maryana N, Hidayat P. 2024. Diversity and foraging activity of coffee insect pollinators in land near and far from the forest of North Sumatra, Indonesia. Biodiversitas 25: 240-248. Coffee (Coffea spp.) is among the plant species that depend on insects to aid in its pollination process, where insect pollinators serve as intermediaries facilitating plant pollination. This study examined the diversity, abundance, and visiting activity of insect pollinators in coffee cultivation located in different areas, specifically those near the forest and those far from the forest in Simalungun District, North Sumatra. The study was carried out from September 2022 to February 2023 in six coffee cultivation sites spread across four sub-districts in Simalungun District, i.e., Silimakuta, Pematang Silimakuta, Purba, and Dolok Silau. The study's results revealed the presence of 16 species of insect pollinators in coffee cultivation near the forest and 13 species in those located far from the forest. The identified insect pollinators species were from Order Hymenoptera; Apis cerana, Lasioglossum sp., Dolichovespula norvegicoides, Diptera; Stomorhina discolor, Musca domestica, Bactrocera papayae, Nephrotoma flavescens, Episyrphus viridaureus, Oebalia sp., Coleoptera; Pachnaeus sp., Cantharis sp., Scarabaeidae sp 1., Maladera japonica, Lepidoptera; Agrotis segetum, Bradina diagonalis, and Nyctemera baulus. Notably, the abundance of coffee insect pollinators was more pronounced in close proximity to the forest compared to areas far from the forest. Regarding the visiting duration of these insects, S. discolor exhibited the longest visit duration of 76.46±1.19 seconds per flower, and the shortest duration in A. cerana was recorded at 8.35±0.23 seconds per flower.